Evolution of Motions of a Rigid Body About its Center of Mass - Chernousko, Felix L.; Akulenko, Leonid D.; Leshchenko, Dmytro D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book presents a unified and well-developed approach to the dynamics of angular motions of rigid bodies subjected to perturbation torques of different physical nature. It contains both the basic foundations of the rigid body dynamics and of the asymptotic method of averaging. The rigorous approach based on the averaging procedure is applicable to bodies with arbitrary ellopsoids of inertia. Action of various perturbation torques, both external (gravitational, aerodynamical, solar pressure) and internal (due to viscous fluid in tanks, elastic and visco-elastic properties of a body) is considered in detail. The book can be used by researchers, engineers and students working in attitude dynamics of spacecraft.
The foundations of dynamics of a rigid body with a fixed point -- Motion of a rigid body by inertia. Euler's case -- Lagrange's case -- Equations of perturbed motion of a rigid body about its center of mass -- Perturbation torques acting upon a rigid body -- Motion of a satellite about its center of mass under the action of gravitational torque -- Motion of a rigid body with a cavity filled with a viscous fluid -- Evolution of rotations of a rigid body in a medium -- Motion of a rigid body with internal degrees of freedom -- Influence of the torque due to the solar pressure upon the motion of a Sun satellite relative to its center of mass -- Perturbed motions of a rigid body close to Lagrange's case.
Keywords: Aerospace engineering; Astronautics; Mathematical physics; Mechanics; Aerospace Technology and Astronautics; Mathematical Physics; Classical Mechanics